ARCHAEOLOGICAL AND ARCHAEOBOTANICAL RESEARCH AT AN EARLY MEDIEVAL SITE IN WILDNO, KUJAWSKO-POMORSKIE VOIVODESHIP - Abramów, Joanna; Wiktor, Arkadiusz (Bulletin of Geography. Physical Geography Series, 2011)
The paper presents the results of the archaeological excavation of the Early Medieval site at Wildno (site 10) and the initial results of ongoing archaeobotanical analysis of plant macro-remains from the same site. During rescue excavation many archaeological features were found. Among them a few probable huts, smokehouses and tar pits were discovered. Inside them, plant macro-remains were found. Analyses showed remains of cultivated plant and weed species, which provides evidence of farming practice during early medieval times. The cultivated plants were Linum usitatissimum, Panicum miliaceum and Triticum aestivum.